Analisis Perbandingan Daya Keluaran PLTS di PLTM Kokok Putih Berdasarkan Data Intensitas Radiasi Matahari Dari Hasil Pengukuran Dan Global Solar Atlas - Sabandi, Rahmat Aprial; Muljono, Agung Budi (Jurnal Energi Baru dan Terbarukan, 2025)
Renewable energy, including solar energy, has become a potential solution to meet the ever-increasing demand for electricity. This study aims to analyze the output power of the Solar Power Plant (PLTS) located at PLTM Kokok Putih, East Lombok, by comparing solar radiation intensity data from direct measurements and the Global Solar Atlas. Measurements were conducted using a lux meter from 09:00 to 15:30, while Global Solar Atlas data covered the entire day. The analysis results show that the average output power from direct measurements is 0.138 kW, while the Global Solar Atlas data yields an average of 0.079 kW, with a difference of 0.059 kW. This discrepancy arises due to differences in time and solar radiation intensity used in the two methods. Moreover, the PLTS location is considered economically viable for operation based on the annual Global Horizontal Irradiation (GHI) value of 1835.8 kWh/m², exceeding the recommended minimum threshold of 1500 kWh/m². This study provides insights into the influence of measurement time and radiation intensity on PLTS output power while affirming the potential of solar energy as a viable electricity source in tropical regions. The research recommends uniform measurement times for more accurate data comparisons.